Évaluation comparée de la pollution des rivières Kahuwa et Mpungwe par l'utilisation des macroinvertébrés benthiques - Dieudonné Zirirane; Jean Jacques Bagalwa; M. Isumbisho; M. Mulengezi; I. Mukumba; M. Bora; J.M. Mucheso; A. Lukamba; G. Iragi; B. Irenge; F. Kibangu; R. Kamangala (VertigO)
The environmental disturbances due to human activities increase in many countries and draw away various types of water pollutions. These pollutions are important and cause a serious regional and local problem in public health. In Bukavu and the surrounding areas, there are enough aquatic systems which shown signs of pollution resulting from human activities. In order to estimate the impact of human activities on the water quality within rivers, this study was carried out in the Kahuwa river, located in Bukavu, urban area, and Mpungwe river, located in rural area, so far at 20 Km of Bukavu. The physico-chemical and biological parameters from 7 sampling sites of both rivers (4 in the Kahuwa river and 3 in the Mpungwe river) was assessed in-situ and in the laboratory of the Lwiro Research Centre in Natural Sciences, Democratic Republic of Congo. According to the results obtained, Kahuwa river is more polluted than Mpungwe river during the period of this study. The physico-chemical parameters reach from upstream to downstream in both rivers Kahuwa and Mpungwe. The nutrients (phosphorus and nitrogen) increased in the sites which is intensively anthropogenic activities (Kibonge, Cheche and SNCC for the Kahuwa river and Murhesa factory for the Mpungwe river). The organic pollution is intensified by anthropogenic used. In general the physico-chemical water quality parameters show a significant difference (p